2003
DOI: 10.1136/bmj.326.7386.426
|View full text |Cite
|
Sign up to set email alerts
|

Relation between hormone replacement therapy and ischaemic heart disease in women: prospective observational study

Abstract: Objective To investigate the risk of ischaemic heart disease and myocardial infarction among women using hormone replacement therapy, especially the potential modifying effect of cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
(20 reference statements)
2
28
1
5
Order By: Relevance
“…Although this phenomenon can be seen in the current study too, the female disadvantage was seen with both absolute and relative measures, and a clearly significant interaction between sex and type 2 diabetes was found. Since the interaction is also supported by a recent Finnish study on the risk of CHD (2), other mechanisms must be working too, such as possible postmenopausal changes in sexual hormones or estrogen replacement therapy (17). Unfortunately, this was not accounted for in the present study.…”
Section: Research Design Andmentioning
confidence: 62%
“…Although this phenomenon can be seen in the current study too, the female disadvantage was seen with both absolute and relative measures, and a clearly significant interaction between sex and type 2 diabetes was found. Since the interaction is also supported by a recent Finnish study on the risk of CHD (2), other mechanisms must be working too, such as possible postmenopausal changes in sexual hormones or estrogen replacement therapy (17). Unfortunately, this was not accounted for in the present study.…”
Section: Research Design Andmentioning
confidence: 62%
“…How the balance of risks and benefits influences outcomes in women with diabetes remains uncertain. Two observational studies have reported a decrease in risk of myocardial infarction associated with current use of estrogen plus progestin among women with diabetes (6,7), whereas a third study has reported an increased risk (8). The purpose of this casecohort study was to determine the association between postmenopausal estrogen therapy and fatal and nonfatal cardiovascular disease among women with type 2 diabetes.…”
mentioning
confidence: 99%
“…Essa estratégia de individualização terapêutica torna-se ainda mais importante quando se refere a subgrupos de pacientes com patologias específicas, como é o caso do DM. Recentemente, estudo observacional mostrou que mulheres com DM em uso de TRH têm maior risco de doença cardiovascular e morte do que mulheres com DM não usuárias de TRH (25), o que reforça a idéia de se buscar alternativas seguras para o alívio de sintomas climatéricos em mulheres com DM.…”
Section: Discussionunclassified